Heterogeneity of DNA fragments associated with the sickle-globin gene. - Feldenzer, J (1979)
We have examined the genetic polymorphism previously reported to be associated with the sickle-cell (beta s) gene. The polymorphism involves an alteration of the DNA sequence 3' to the beta-globin gene as detected with the restriction endonuclease, Hpa I. In normal individuals, the beta-globin gene is contained within a DNA fragment of 7.6 kilobases (kb), whereas 87% of individuals with sickle-cell anemia have been reported to have the beta s-gene associated with a 13.0-kb Hpa I fragment. We have studied this polymorphism in 31 New York Black individuals homozygous for sickle-cell anemia to ascertain its genetic and biochemical significance and to evaluate its potential use in the prenatal diagnosis of sickle-cell disease. Our results show only a 58% association of the beta s-gene and the 13.0-kb Hpa I fragment, as well as the presence of additional variants involving the Hpa I site. In addition, the 13.0-kb fragment is also found associated with the beta c- and beta A-genes. Thus, the Hpa I polymorphism probably represents a change in DNA not specifically associated with the beta s-gene, and appears to antedate the beta s-and beta c-mutations.